The effects of different small-sided games configurations on heart rate, rating of perceived exertion, and running demands in professional soccer players - Gantois, P.; Piqueras-Sanchiz, F.; Cid, M. J. F. A.; Pino-Ortega, J.; Castillo, D.; Nakamura, F. Y. (European Journal of Sport Science, 2023)
We examined the effects of different small-sided games (SSG) configurations on heart rate (HR), rating of perceived exertion (RPE), and running demands in soccer players. Twelve male soccer players (U18) participated in this randomized cross-over study. Players performed three SSG in different "fixed" and "dynamic" pitch sizes (3v3 in large (SSGL) and small (SSGS) fixed area; or 3v3 in dynamic dimensions [SSGD]), with 4x4 minutes interspersed by 2 minutes of rest. HR measures (maximum [HRmax], average [HRavg], and percentage of maximum [%HRmax]), RPE, and running demands were collected across the SGG sessions. The following running activities were recorded: total distance covered (TD), distance covered (DC) at 6-12 km·h-1, = 12-18 km·h-1, and >18 km·h-1, peak running speed, acceleration (ACC) and deceleration (DEC) at 1-2 m·s-2 and 2-3 m·s-2, player load, and high metabolic load distance (HMLD). SSGL displayed higher HRavg, %HRmax, and RPE values than SSGS (p < 0.05). SSGL resulted in higher TD, DC at 6-12 km·h-1, = 12-18 km·h-1, > 18 km·h-1, and higher peak speed than SSGS and SSGD (p < 0.05). Moreover, SSGD presented higher TD and DC at 6-12 km·h-1 and = 12-18 km·h-1 than SSGS (p < 0.05). In contrast, SSGD and SSGS showed higher number of ACC and DEC at 1-2 m·s-2 than SSGL (p < 0.05). In conclusion, the pitch size and playing area of the SSG can be manipulated to promote desired physiological and physical demands in young soccer players.